Antioxidants restore store‐operated Ca2+ entry in patient‐iPSC‐derived myotubes with tubular aggregate myopathy‐associated Ile484ArgfsX21 STIM1 mutation via upregulation of binding immunoglobulin protein - Fusako Sakai‐Takemura; Fumiaki Saito; Ken'ichiro Nogami; Yusuke Maruyama; Ahmed Elhussieny; Kiichiro Matsumura; Shin'ichi Takeda; Yoshitsugu Aoki; Yuko Miyagoe‐Suzuki (FASEB BioAdvances, 2023)
Abstract Store‐operated Ca2+ entry (SOCE) is indispensable for intracellular Ca2+ homeostasis in skeletal muscle, and constitutive activation of SOCE causes tubular aggregate myopathy (TAM). To understand the pathogenesis of TAM, we induced pluripotent stem cells (iPSCs) from a TAM patient with a rare mutation (c.1450_1451insGA; p. Ile484ArgfsX21) in the STIM1 gene. This frameshift mutation produces a truncated STIM1 with a disrupted C‐terminal inhibitory domain (CTID) and was reported to diminish SOCE. Myotubes induced from the patient's‐iPSCs (TAM myotubes) showed severely impaired SOCE, but antioxidants greatly restored SOCE partly via upregulation of an endoplasmic reticulum (ER) chaperone, BiP (GRP78), in the TAM myotubes. Our observation suggests that antioxidants are promising tools for treatment of TAM caused by reduced SOCE.